Spectral amplitude coding OCDMA using AND subtraction technique - Syed Alwee Aljunid, Syed Junid; M., Othman; N.S.M., Shah; Samad, M.D.A.; Sahabudin, R.K.Z.; Mohamad Khazani, Abdullah (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org